Assessment of Serum Calcium, Phosphorus, and Magnesium in Women with Hypothyroidism: A Cross-sectional Study - Janice D’Sa; H. G. Arpitha; M. B. Prathima; P. Sushith; Greeshma B. Kotian; Suriyan S. Nair (International Journal of Advanced Medical and Health Research)
Context: Thyroid dysfunction, particularly hypothyroidism, is a significant global health concern, especially among women. Thyroid hormones are vital for bone metabolism, influencing serum calcium and phosphorus levels and increasing osteoporosis risk. However, the association between thyroid dysfunction and serum magnesium, essential for immunity and inflammation, remains underexplored. Aims: This study aimed to compare serum calcium, phosphorus, and magnesium levels between women with hypothyroidism and apparently healthy controls. In addition, we aimed to examine the correlations between levels of these electrolytes and thyroid hormones like triiodothyronine (T3), thyroxine (T4), and thyroid-stimulating hormone (TSH). Settings and Design: The cross-sectional study was conducted at a tertiary health care center in Mangalore, India. Methods: The study involved 45 women with hypothyroidism and 45 age-matched apparently healthy controls. Adult participants (18–55 years) were included. We excluded those with conditions affecting mineral metabolism, recent thyroid surgery, pregnancy, or specific medication use. Serum T3, T4, TSH, calcium, phosphorus, and magnesium levels were estimated using the standard techniques. Statistical Analysis Used: Independent samples t-test, Chi-square test, and Pearson’s correlation test. Statistical significance was considered at P < 0.05. Results: Serum calcium was lower in women with hypothyroidism, whereas magnesium and phosphorus levels were higher (P < 0.001 for all comparisons). Positive correlation between serum calcium and T4 levels and negative correlations of magnesium and phosphorus with T4 levels were observed. Serum TSH showed a negative correlation with calcium and a positive correlation with magnesium levels. Conclusions: Women with hypothyroidism exhibit decreased serum calcium and increased serum magnesium and phosphorus levels in relation to their counterparts. Women with hypothyroidism exhibit altered mineral metabolism, emphasizing the need for comprehensive management addressing both hormonal and mineral imbalances.